Efficacy of selected pesticides and biopesticides against major pest infesting Solanum melongena L. - Nurin Izzati Mohd Zulkifli,; Saiful Zaimi Jamil,; Aimi Athirah Ahmad,; Mohd Shahidan Shohaimi,; Mohd Masri Saranum,; Siti Noor Aishikin Abdul Hamid,; Umikalsum Bahari, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Terung Telunjuk also known as Terung Kuning (Solanum melongena L.), is an edible fruit belonging to the family Solanaceae, one of the largest families in vegetables. Even though identification of the major pests of S. melongena has been widely done, however information about the management of these pests remains scarce. Therefore, the objective of this study was to evaluate the effectiveness of selected biopesticides and insecticides (application type) and spraying time (before and after application) against these insect pests’ population of Terung Telunjuk. Experiments were laid out in a Randomized Complete Block Design (RCBD) with three replications and eight treatments. A two-way analysis of variance (ANOVA) was used to evaluate the influence of two independent variable (application type, spraying time) on the number of sucking insects found on Terung Telunjuk. The application treatments were: (T1) garlic oil; (T2) neem oil; (T3) Pest Guard™; (T4) Shelter X™; (T5) wood vinegar; (T6) Confidor™; (T7) Abenz™ and (T8) control (water only), respectively. Result showed that there is significant difference on the application type on number of sucking pest (df=7, F=2.95, p<0.05). On the other hand, spraying time yielded (df=1, F=0.18, p>0.05) indicate that the effect of spraying time was not significant. Similarly, the interaction effect between application type and spraying time was also not significant [df=7, = 0.28, p>0.05]. There was no significant different between the spraying time (p>0.05), indicating that there were no differences in the total number of sucking insects before and after spraying. Confidor was found to be the most effective treatment to control sucking pest. Whereas the wood vinegar and neem oil did were between the application treatments toward borer insects, surprisingly, neem oil recorded the lowest number of damage/infected fruits. Information gained from this study may be used as a baseline for future insect pest and biological control related studies on other Solanaceae including the traditional vegetables.